Pendampingan Siswa dalam Penguatan Dan Pelestarian Batik Madura melalui Pendekatan Rumah Kreatif di Pulau Madura - Farahdilla Kutsiyah (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2019)
This article aims as an early effort to strengthen and regenerate the tradition of Madura written batik through creative-integrative education, creative intelligent character education and play creativity. Student assistance is began by selection of a region (village) as a target for the implementation of Integrative Creative Education (Creative House) by referring to the potential of batik in the area / village with the One Village One Product (OVOP) approach. Second, Focus discussion group (FGD) with local stakeholders. Third, data inventory of elementary and middle school children who have the talent for batik. Fourth, determine syllabus, teaching materials, main activities, facilities and infrastructure. Fifth, the application of community homeschooling with an orientation to developing the potential of children who have a hobby of batik, both physically, mentally and spiritually and facilitating the development of their interests. Sixth, open a inovative space for young people to be creative by carrying out the halal lifestyle through syar'i fashion and tourism based on Madura batik.